Pelatihan Ecoprint Berbasis Tumbuhan Lokal: Penguatan Kreativitas dan Minat Kewirausahaan Siswa MIN 1 Soppeng - Harti Oktarina; Irham Maulana Yunus; Muh. Yunus; Ninah Wahyuni A; Sitti Hajar Aswad (Yayasan Daarul Huda Kruengmane, 2026)
Creativity, environmental awareness, and an entrepreneurial orientation should be fostered through concrete learning experiences from primary education. This community engagement program aimed to improve students’ ecoprint-making skills, creativity, and entrepreneurial interest through the use of local plants. The training was conducted on 24 November 2025 at MIN 1 Soppeng, South Sulawesi, and involved 20 students in Grades IV–VI. A participatory, learning-by-doing approach was employed, consisting of coordination, an introduction to ecoprint and product value, a pounding-technique demonstration, group practice, and evaluation. Product observation and a 1–4 pre- and post-activity questionnaire were used. The report recap indicates that the mean entrepreneurial-interest score increased from 2.8 to 3.6 (28.6%), while creativity increased from 3.0 to 3.7 (23.3%). Sixteen of the 20 students showed improved entrepreneurial-interest scores. All participants completed the tote-bag production stages and produced varied leaf-based compositions. Ecoprint training may serve as a contextual project integrating art, environmental education, and early entrepreneurship. Program continuity requires teacher mentoring, a standardized product rubric, and evaluation based on documented individual-level data.